2015
DOI: 10.1098/rsif.2014.0899
|View full text |Cite
|
Sign up to set email alerts
|

Constructing predictive models of human running

Abstract: Running is an essential mode of human locomotion, during which ballistic aerial phases alternate with phases when a single foot contacts the ground. The spring-loaded inverted pendulum (SLIP) provides a starting point for modelling running, and generates ground reaction forces that resemble those of the centre of mass (CoM) of a human runner. Here, we show that while SLIP reproduces within-step kinematics of the CoM in three dimensions, it fails to reproduce stability and predict future motions. We construct S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 33 publications
5
66
0
Order By: Relevance
“…As noted in the introduction, our approach differs from others in constraining force, kinematics and stance duration: In some studies such as in the virtual pivot models [31], only GRFs are considered leading to model parameters that are in clear conflict with the animal's COM motion as no restriction is placed on the height of the COM. Other studies normalize time to stance duration [10], allow stance time to vary [30], or only focus on fitting the COM trajectory (vertical height as a function of the horizontal displacement) [32].…”
Section: Theoretical Fits To Experimental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in the introduction, our approach differs from others in constraining force, kinematics and stance duration: In some studies such as in the virtual pivot models [31], only GRFs are considered leading to model parameters that are in clear conflict with the animal's COM motion as no restriction is placed on the height of the COM. Other studies normalize time to stance duration [10], allow stance time to vary [30], or only focus on fitting the COM trajectory (vertical height as a function of the horizontal displacement) [32].…”
Section: Theoretical Fits To Experimental Datamentioning
confidence: 99%
“…That is, a successful model must produce realistic GRFs within the constraints of experimentally observed COM kinematics over experimentally observed stance duration. These three constraints are rarely satisfied [31,30,32] simultaneously in most studies of locomotion. Without satisfying the constraints on force, kinematics and duration simultaneously, the problem is under constrained: The COM height determines the natural timescale of the system (∼ R nat /g); and, in understanding locomotion, one important consideration is how does the stance duration compare to the natural time constant.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have noted that done naively, the observed eigenvalues change with phase 14, 35-37 -a result contrary to theory (see §2). Estimating the return map by using multiple Poincaré sections simultaneously 35,37 improves the reliability of the results.…”
Section: The Toolbox Of Data Driven Floquet Analysismentioning
confidence: 96%
“…We recently used DDFA to provide evidence in support of a 2009 prediction 38 that control of human running allows complete ("dead-beat") recovery within 2 steps. 37 We also used the DDFA to produce a linearized controller model for the human, 37 which could then be reduced into low dimensional "factors", allowing us to identify that by adding the state of the swing-leg ankle to the existing model's state-space the predictive ability of the model could be greatly improved.…”
Section: The Toolbox Of Data Driven Floquet Analysismentioning
confidence: 99%
“…Our work revolves around the spring-loaded inverted pendulum (SLIP) model, a hybrid dynamic model ubiquitous in both biomechanics and the robotic legged-locomotion community for modeling running or hopping gaits. This model can be fit very accurately to experimental data of many different running animals [17] [18], allows accurate prediction [19], and also has been used to design controllers for simulations [20][21] [22][23] as well as actual robots [24][25] [26]. Indeed, there has been a lot of effort to give legged robots SLIP-like behavior, either through mechanical design [27] [28] or control [24] [29].…”
Section: Viability Kernel Of a Running Model A Modelmentioning
confidence: 99%